SIRT1 Suppresses Activating Transcription Factor 4 (ATF4) Expression in Response to Proteasome Inhibition - Woo, S.R., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Park, J.E., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Kim, Y.H., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Ju, Y.J., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Shin, H.J., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Joo, H.J., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Park, E.R., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Hong, S.H., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea; Park, G.H., Korea University, Seoul, Republic of Korea; Lee, K.H., Korea Institute of Radiological and Medical Sciences, Seoul, Republic of Korea (Journal of microbiology and biotechnology, 2013)
The synthetic machinery of ATF4 (activating transcription factor 4) is activated in response to various stress conditions involved in nutrient restriction, endoplasmic reticulum homeostasis, and oxidation. Stress-induced inhibition of proteasome activity triggers the unfolded protein response and endoplasmic reticulum stress, where ATF4 is crucial for consequent biological events. In the current study, we showed that the NAD+-dependent deacetylase, SIRT1, suppresses ATF4 synthesis during proteasome inhibition. SIRT1 depletion via transfection of specific siRNA into HeLa cells resulted in a significant increase in ATF4 protein, which was observed specifically in the presence of the proteasome inhibitor MG132. Consistent with SIRT1 depletion data, transient transfection of cells with SIRT1-overexpressing plasmid induced a decrease in the ATF4 protein level in the presence of MG132. Interestingly, however, ATF4 mRNA was not affected by SIRT1, even in the presence of MG132, indicating that SIRT1-induced suppression of ATF4 synthesis occurs under post-transcriptional control. Accordingly, we propose that SIRT1 serves as a negative regulator of ATF4 protein synthesis at the post-transcriptional level, which is observed during stress conditions, such as proteasome inhibition.